PERANCANGAN SISTEM PAKAR DETEKSI PENYAKIT FUS PADA KUCING DENGAN METODE DEMPSTER SHAFER BERBASIS WEBSITE - Qori Istiqomah (2020)
FUS disease is an inflammation of the urinary bladder in cats. It has several types and symptoms. Many cats owners lack of knowledges about FUS disease and the symptoms. Many cat owners in Indonesia do not treat their cat like the way they treat human. For example, when their cats sick, they will bring their cats to the vet and where they wil get more quality food which have quite expensive cost. In current technological advances, especially in computer technology. In Indonesia, the availability of veterinarians and veterinary clinics are quite less available. To overcome this problem, technology of computer is needed, because the technology are growing fastly, especially technology of computer. It is then used to create and develop the expert system, because the expert system is the system which is used to decide choices. Furthermore, this expert system is mainly used for people having cats who lack of knowledge about FUS disease in cats, so that they know whether their cats are infected or not and they will also know how to overcome it. This study aims to implement the Dempster Shafer Method in the FUS disease detection system in cats. This method is a place for the expert to give a value of trust in the given knowledge. In this designed system, the expert system uses the dempster shafer algorithm for counting the value of trust in the cats symptoms. This study results about 96,1% of dempster shafer average counting based on the experiment which is done.